Człowiek/zwierzę/roślina/maszyna - perspektywa posthumanistyczna - Gajewska, Grażyna (Studia Europaea Gnesnensia, 2011)
The article deals with the cultural and contextual complexity of the ideas concerning posthumanity. The main problem is the formulation of a scope of the new subjec-tivity which is neither hierarchical, nor homogeneous.